Process and Outcome Evaluation of the Gang Resistance Education and Training (G.R.E.A.T.) Program, 2006-2011 (UNITED STATES) - Esbensen, Finn-Aage ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The goal of the study was to determine what effect, if any, the Gang Resistance Education and Training (G.R.E.A.T.) program had on students. The G.R.E.A.T., a 13-lesson general prevention program taught by uniformed law enforcement officers to middle school students, had three stated goals: 1) to reduce gang membership, 2) to reduce delinquency, especially violent offending, and 3) to improve students' attitudes toward the police. To assess program effectiveness, researchers conducted a randomized control trial involving 3,820 students nested in 195 classrooms in 31 schools in 7 cities. A process evaluation consisted of multiple methods to assess program fidelity: 1) observations of G.R.E.A.T. Officer Trainings, 2) surveys and interviews of G.R.E.A.T.-trained officers and supervisors, 3) surveys of school personnel, and 4) "on-site," direct observations of officers delivering the G.R.E.A.T. program in the study sites. Only the data from the student surveys, law enforcement officer surveys, and school personnel surveys are available. Data file 1 (Student Survey Data) has 3,820 cases and 1,926 variables. Data file 2 (Law Enforcement Survey Data) has 137 cases and 140 variables. Data file 3 (School Personnel Survey Data) has 230 cases and 148 variables.